ANALISIS KARAKTER RELIGIUS MURID MELALUI BUDAYA SEKOLAH KELAS IV SD MUHAMMADIYAH KUTOARJO - Candra listi Rahmani; Nur Ngazizah; Rintis Rizkia Pangestika (STKIP Subang, 2024)
Religious character is an essential foundation that every student should possess. This study aims to describe the religious character of students through school culture in the fourth grade of SD Muhammadiyah Kutoarjo. This research uses a descriptive qualitative method with eight fourth-grade students from the 2024/2025 academic year as subjects, categorized as advanced, competent, proficient, and emerging. Data collection techniques include observation, interviews, questionnaires, and documentation. The data were analyzed using data reduction, data display, and conclusion verification techniques. The results of the study show variations in the implementation of religious character among students. Students in the advanced category (S1) have a high awareness of the importance of prayer, memorize four surahs, recite the Quran on time, and always perform congregational prayers. Students in the competent category (S2) carry out religious duties but tend to be motivated by sanctions. Students in the proficient category (S3) have good religious habits, although not yet fully consistent. Meanwhile, students in the emerging category (S4 to S8) show a lack of religious awareness, with some students reluctant to perform prayers, recite the Quran, and join congregational prayers.This study concludes that the religious character of students is formed through school culture, although the level of awareness and consistency in its implementation varies among students.